PENGARUH PENDEKATAN KONSTRUKTIVISME TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI KELAS IV SD NEGERI 4 TUGUMULYO - Refi Arista; Destiniar; Putri Dewi Nurhasana (STKIP Subang, 2023)
The study aims to determine whether there is any effect of the constructivism approach on geometric shapes on student learning outcomes in class IV SD Negeri 4 Tugumulyo. This research is a type of quantitative research using the Pre-Experimental type Experimental method with the One-Group Pretest-Posttest Method design. The variables of this study consist of the independent variable (X), namely the Constructivism Approach and the dependent variable (Y), namely the results of learning Mathematics. The population in this study were all fourth grade students at SDN 4 Tugumulyo, totaling 30 students. The sample of this research is students of class IV, totaling 30 students. The data collection technique in this study was a question test in the form of 10 multiple choice questions. The results of this study indicate that the pretest (initial test) of students' knowledge has an average value of 46.44 in the less good category, after being given treatment using the constructivism approach the final test results (posttest) show an average value of 80.33 in the good category and experiencing enhancement. Obtained Tcount = 19.561 > Ttable = 1.671 with a significant level of α = 0.05, (Tcount = 19.561 > Ttable = 1.671) according to the criteria for testing the hypothesis if Tcount > Ttable then Ho is rejected and Ha is accepted. Thus there is an effect of the use of a constructivist approach to flat shape material on student learning outcomes in class IV. Keywords: Constructivism, Flane figure, Learning Outcomes